Problem of Collateral Damage to Population of a State - Object of International Economic Sanctions - D. A. Zhukov; V. R. Atnashev (Евразийская интеграция: экономика, право, политика, 2019)
The article considers the problem of collateral damage to population in the implementation of the regime of international economic sanctions. The author tries to define the concept and features of collateral damage to population. Ways to minimize consequences for population are also identified by the author.